2014
DOI: 10.1189/jlb.1mr0114-068r
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid P: a systemic regulator of the innate immune response

Abstract: The pentraxin SAP reduces neutrophil adhesion to ECM proteins, inhibits the differentiation of monocytes into fibrocytes, attenuates profibrotic macrophages, activates the complement pathway, and promotes phagocytosis of cell debris. Together, these effects of SAP regulate key aspects of inflammation and set a threshold for immune cell activation. Here, we present a review of SAP biology with an emphasis on SAP receptor interactions and how the effect of SAP on monocytes and macrophages has been explored to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 70 publications
2
67
0
Order By: Relevance
“…Fibrocytes also promote angiogenesis by secreting VEGF, bFGF, IL-8, and PDGF and promote fibroblast proliferation, migration, and collagen production by secreting TGF-β and CTGF (13,14). Fibrocyte recruitment and differentiation is regulated by a variety of factors (3,15). In vitro, monocytes can differentiate into fibrocytes without the addition of any exogenous factors (5,11,12,(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Fibrocytes also promote angiogenesis by secreting VEGF, bFGF, IL-8, and PDGF and promote fibroblast proliferation, migration, and collagen production by secreting TGF-β and CTGF (13,14). Fibrocyte recruitment and differentiation is regulated by a variety of factors (3,15). In vitro, monocytes can differentiate into fibrocytes without the addition of any exogenous factors (5,11,12,(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…fibrocyte | lumican | fibrosis | inflammation | decorin D uring wound healing, monocytes leave the circulation, enter the tissue, and differentiate into fibroblast-like cells called fibrocytes (1)(2)(3)(4)(5)(6). Fibrocytes are also found in the scar tissue-like lesions associated with fibrotic diseases such as pulmonary fibrosis, congestive heart failure, cirrhosis of the liver, and nephrogenic systemic fibrosis (3,(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Preclinical cell and animal experiments suggested that SAP could reduce bleomycin-induced lung fibrosis 38,[83][84][85] . Intravenous administration of recombinant form of human SAP (PRM-151) resulted in a 30-50% decrease in fibrocyte numbers 24 h post-dose in pulmonary fibrosis patients 86 .…”
Section: Potential Therapy Targeted On Circulating Fibrocyte and Cxcr4mentioning
confidence: 99%